Optimizing Career Interests in The Field of Taxation: The Role of Economic Motivation and Understanding Tri Nga Teaching - Sri Lestari Yuli Prastyatini; Uum Helmina Chaerunisak; Reni Listyawati; Indriyati Eko Purwaningsih; Frendika R D (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2024)
This research aims to empirically prove whether economic motivation and the understanding of Ki Hadjar Dewantara's teachings, Tri-Nga, can influence career interest in the taxation field. The population of this study is accounting students of Universitas Tamansiswa throughout Indonesia. Convenience sampling technique was used to collect the sample, and a total of 188 respondents were obtained. This type of research is quantitative research using primary data. Data collection was carried out using questionnaires distributed to all accounting students of Universitas Tamansiswa throughout Indonesia. Data processing was carried out using multiple linear regression analysis. The results of the study show that economic motivation and the understanding of Ki Hadjar Dewantara's teachings, Tri-Nga, have a significant partial positive effect on students' interest in pursuing a career in taxation. The implications of this study are that graduates will pursue careers in taxation by considering the element of economic motivation obtained through income or wages. In addition, understanding Tri-Nga is the most fundamental element so that students can decide to pursue a career in taxation. The novelty of this research is the addition of the Tri-Nga variable as an independent variable, and it also answers the differences in the results of previous research on this topic.Keywords: Career interest, motivation, Tri-Nga teaching.